(untitled) (Journal of Pharmaceutical Negative Results, 2023)
Chicken meat is easily damaged due to physical and chemical quality damage. Bay leaves contain flavonoid compounds that can help preserve meat, have antimicrobial properties, and have good nutrition. The aim of this study was to identify the physicochemical quality of broiler meat that had been treated with bay leaf solution during cold storage and its relationship to the sensory effects of the resulting nuggets. This study used broiler meat soaked in three concentrations of bay leaves, namely 0, 15, and 30%, and then stored in the refrigerator. Measurements of meat quality and nugget production were carried out on days 0, 2, and 4 of storage. The study used a 3x3 factorial, complete randomized design (3 concentrations of bay leaf solution and 3 storage periods). The parameters measured were the physicochemical quality of the meat (cooking loss and water holding capacity) and the sensory quality of the nuggets (level of preference). The results showed that soaking meat at a concentration of 15% bay leaf increased its water holding capacity with storage time (P<0.01) and increased cooking losses with storage time (P<0.01). The storage time of the meat had no effect on the preference level of the resulting nuggets.Soaking the meat in a bay leaf solution at a concentration of 15% increased the sensory quality of the nuggets (P<0.01), while storing the meat for up to 4 days in the refrigerator increased its water holding capacity and cooking shrinkage.